قبل ازاسلام عرب کی مشہور تجارت اورتجارتی مراکز کا تجزیاتی مطالعہ: An Analytical Study of the Famous Trade and Commercial Centers of Pre-Islamic Arabia (Al-Aasar, 2025)
Before the advent of Islam, the Arabian Peninsula was a significant hub for trade and commerce. The region's strategic location between Asia, Africa, and Europe made it an essential part of global trade routes. Major trade centers such as Mecca, Medina, Ta’if, and Yemen played a crucial role in facilitating the exchange of goods like spices, perfumes, textiles, and precious metals. The pre-Islamic Arabs were skilled merchants, utilizing caravan trade routes and sea trade via the Red Sea and the Persian Gulf. This study analyzes the economic activities of pre-Islamic Arabs, their trade mechanisms, and the impact of these commercial activities on social and political structures. The research highlights how trade contributed to the wealth and influence of certain tribes, particularly the Quraysh, who dominated Meccan trade. Furthermore, it explores the role of seasonal fairs and marketplaces, such as 'Ukaz and Dhu al-Majaz, in promoting cultural and economic interactions. Understanding the pre-Islamic Arabian trade system provides valuable insights into the economic foundation upon which Islamic civilization later flourished.